Multi-stakeholder perspectives on cervical cancer screening implementation in Indonesia: A qualitative study of cervical screening barriers in Banda Aceh - Yolanda, Febrina; Dewi, Tgk. Puspa; Nainggolan, Sarah I.; Munawar, Munawar; Munizar, Munizar; Bulqini, Rijal; Suhanda, Rachmad; Rusnaidi, Rusnaidi (Narra J, 2026)
Indonesia is committed to the WHO's cervical cancer elimination strategy through the National Action Plan (RAN) 2023–2030, targeting 75% screening coverage by 2030. However, current rates remain critically low at 7.02%. This study explores multi-stakeholder perspectives to identify implementation barriers and facilitators for policy enhancement. A qualitative descriptive case study was conducted in Banda Aceh (July-August 2025) involving 25 stakeholders: City Health Office Head, 11 puskesmas heads, 11 VIA coordinators and 2 community organization representatives. Thematic analysis using NVivo v.16 identified key implementation factors. Five major themes emerged: (1) Knowledge gaps—screening perceived necessary only when symptomatic despite available information; (2) Access paradox—excellent geographic access and flexibility undermined by limited examination rooms, insufficient midwives, and psychosocial barriers (shame, fear, lack of spousal support); (3) Financial sustainability—free services threatened by complex BPJS claims and low reimbursement affecting logistics; (4) Service quality variation—dependent on cross-sector collaboration and staff competency, with uneven training and limited cryotherapy (only 2 centers); and (5) Communication challenges—inconsistent digital media use necessitates face-to-face counseling and cadres, though reach remains limited. Implementation faces psychological barriers, capacity limitations, and uneven digital adoption despite strong infrastructure. Priority policy recommendations include: (1) HPV DNA self-sampling to overcome privacy barriers; (2) simplified BPJS claims with adequate reimbursement; (3) systematic competency-building and cryotherapy expansion; and (4) culturally-adapted education integrating local language and religious leaders. These evidence-based enhancements could accelerate Indonesia's RAN 2030 elimination targets.